A Survey of Mealybugs and Associated Natural Enemies in Vineyards in the Western Cape Province, South Africa - Walton, V.M.; Pringle, K.L. (South African Journal of Enology and Viticulture, 2017)
A survey of mealybugs and their associated natural enemies occurring in vineyards was conducted in the Western Cape Province during the 1999/2000 and 2000/2001 seasons. Planococcus ficus (Signoret) was the dominant mealybug and was found for the first time on roots of grapevines. This has far-reaching implications for the control of this important vine leafroll virus vector as control measures have been focused on above-ground control. Other mealybugs recorded on vines were Pseudococcus longispinus (Targioni-Tozzetti) and Ferrisia malvastra (McDaniel). Pseudococcus viburni (Maskell) and Ps. solani Ferris were found on weeds in vineyards. The more frequently recorded natural enemies of P. ficus were species of Nephus predatory beetles and the parasitoids, Coccidoxenoides perminutus Girault, Anagyrus sp. and Leptomastix dactylopii (Howard).